Molecular Interactions in Binary Liquid Mixtures of Cyclohexanone with Morpholine, Bromobenzene and Anisole at 308.15 K and 318.15 K - Rose Venis, A.; Rosario Rajkumar, X. (Asian Journal of Chemistry, 2014)
Densities, viscosities and ultrasonic velocities have been measured for the binary mixtures of cyclohexanone with morpholine, bromobenzene and anisole at 308.15 K and 318.15 K over the entire range of mole fraction. Thermodynamic parameters like excess volume, adiabatic compressibility, free volume, linear free energy, acoustic impedance and viscosity are calculated. From these values the excess properties are also calculated. The deviations of the liquid mixture from ideality have been explained based on the nature molecular interactions between unlike molecules.